Prediction method of extrusion cracking behavior of structural adhesives
Through the stress scanning and flow device test of the wind power structure glue sample, it predicts whether it will occur during the curing process, solve the problem of lack of prediction methods in the existing technology, and realize the rapid optimization of structural glue formula and The safety and economic improvement of wind power blades.
Patent Information
- Application Number
- CN202411214901.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-02
AI Technical Summary
The prior art lacks a method for predicting the extrusion cracking behavior of wind power structural adhesives during curing, which makes it difficult to detect bonding defects in a timely manner, affecting the operational safety and economicality of wind power blades.
A method for predicting the extrusion cracking behavior of structural adhesives is provided, which includes preparing structural adhesive samples, conducting stress scanning tests and rheometer extrusion cracking tests, and predicting whether structural adhesives are prone to cracking behavior by analyzing test data.
The accurate prediction of structural glue crushing and cracking behavior is achieved, helping understand the mechanism of defects, quickly optimize the formula, avoid adhesion defects, and improve the operational safety and economy of wind power blades.
Smart Images

Figure CN118730889B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of structural adhesive performance detection, and in particular to a method for predicting extrusion cracking behavior of structural adhesive. Background Art
[0002] As the core component of a wind turbine, the reliability of its structure directly determines the operational safety of the wind turbine. Under the pressure of cost reduction in the industry, the development of wind turbine blade length and weight poses greater challenges to its structural safety design and material application.
[0003] Wind turbine blades are mainly formed by bonding the front and rear edges of the shell and the web of the main beam using the main beam system as the supporting structure. Wind turbine blades are mostly produced by a step-by-step mold-closing process, in which web bonding is a key step in the mold-closing stage. As the shear web, which is a key component for connecting and transferring loads to the wind turbine blade shell, its bonding quality is a key factor in determining the service life of the blade. During the curing and bonding process of wind turbine blades, the blade shell will undergo thermal expansion and uneven heating at the curing temperature, causing the bonding gap to change as the curing reaction proceeds. This gap change often causes the structural adhesive that plays a bonding role to crack in the body. If structural adhesive extrusion cracking is found during web bonding or wind turbine blade mold-closing, it is often necessary to repair the wind turbine blade by secondary destruction. If the structural adhesive extrusion cracking behavior is not discovered and detected in time during the bonding and mold-closing of wind turbine blades, it may cause more serious economic losses in the later stage. In addition, wind turbine blades will experience vibration and bumps during long-term sea and land transportation, and this bonding defect will increase the possibility of structural damage to wind turbine blades during transportation. For example, during the operation of wind turbine blades, cracking of the structural adhesive body is more likely to induce structural damage to the wind turbine blades, which may cause structural cracks at the mildest and breakage of the wind turbine blades at the worst.
[0004] There is no prediction method for the extrusion cracking behavior of wind power structural adhesives in the prior art. Therefore, we hope to invent a simple, fast and accurate testing method that can predict whether the product may experience extrusion cracking during actual application at the beginning of the wind power structural adhesive formula design. When problems occur with the product, this prediction method can also be used to quickly optimize the formula. Summary of the invention
[0005] The purpose of the present invention is to solve the above-mentioned problems and provide a method for predicting the extrusion cracking behavior of structural adhesives, which can predict in advance whether the structural adhesives will crack, facilitate understanding the mechanism of structural adhesive defects, and quickly optimize the formula according to the mechanism of structural adhesive defects.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for predicting the extrusion cracking behavior of a structural adhesive, the prediction method comprising:
[0007] S0: Preparation of structural adhesive samples;
[0008] S1: performing a stress scanning test on the structural adhesive sample to obtain first test data;
[0009] The first test data includes a yield transition curve and a yield stress value of the structural adhesive sample, and whether the structural adhesive sample is prone to cracking is determined based on the first test data;
[0010] S3: placing the structural adhesive sample on a rheometer test fixture; setting a temperature program and a pressing time and a pressing speed of the test fixture on the rheometer to perform an extrusion cracking test on the structural adhesive sample to obtain second test data;
[0011] The second test data includes whether the structural adhesive sample cracks during the extrusion process, the cracking time of the structural adhesive sample during the extrusion process, and the cracking degree of the structural adhesive sample during the extrusion process. The extrusion cracking behavior of the structural adhesive sample is predicted based on the second test data.
[0012] Optionally, judging whether the structural adhesive sample is prone to cracking according to the first test data in step S1 includes:
[0013] When the stress applied to the structural adhesive sample is greater than the yield stress value, and the yield transition curve does not undergo an obvious mutation, it is judged that the structural adhesive sample is not prone to cracking;
[0014] When the stress applied to the structural adhesive sample is greater than the yield stress value and the yield transition curve undergoes an obvious mutation, it is determined that the structural adhesive sample is prone to cracking.
[0015] Optionally, in the extrusion cracking test of step S3, a material plate of the same material as that of a wind turbine blade is provided, and the surface roughness and surface properties of the material plate are the same as those of the wind turbine blade; the material plate is cut into a first prefabricated plate, and the first prefabricated plate is fixed on a test fixture of a rheometer; and the structural adhesive sample is placed on the first prefabricated plate.
[0016] Optionally, the step S2 further comprises: setting a temperature program on the rheometer, wherein the temperature program comprises a first heating program and a first temperature rising program;
[0017] The first heating program is used to control the heating of the rheometer so that the temperature of the structural adhesive sample reaches 30°C-55°C, and the first heating program is used to control the heating of the rheometer so that the temperature of the structural adhesive sample rises to 55°C-110°C;
[0018] The preheating time of the structural adhesive sample is set on the rheometer to 2 min-30 min.
[0019] The pressing rate of the test fixture on the rheometer is set to 0.3um / s-4.2um / s and the pressing time is set to 10min-60min. The test fixture performs an extrusion cracking test on the structural adhesive sample according to the set pressing rate and pressing time to obtain the second test data.
[0020] Optionally, after predicting the extrusion cracking behavior of the structural adhesive sample according to the second test data, the method further includes step S3:
[0021] When the structural adhesive sample does not exhibit extrusion cracking behavior during the extrusion process, the structural adhesive sample is verified using a device that simulates on-site bonding of the structural adhesive to determine whether the predicted result is accurate.
[0022] Optionally, the device for simulating on-site bonding of structural adhesive comprises a pressing mechanism and a heating mechanism that are arranged relatively to each other, the pressing mechanism has a pressing plate, and the heating mechanism has a heating disk;
[0023] The step S3 comprises: fixing a second prefabricated plate on the pressing plate, fixing a third prefabricated plate on the heating plate, and the sizes of the second prefabricated plate and the third prefabricated plate are both larger than the size of the first prefabricated plate;
[0024] The structural adhesive sample is placed on the third prefabricated plate, and the heating plate is used to heat the structural adhesive sample; the pressing mechanism drives the pressing plate and the second prefabricated plate to press down to squeeze the structural adhesive sample;
[0025] The structural adhesive sample is verified by determining whether cracking occurs in the structural adhesive sample after extrusion.
[0026] Optionally, the heating plate in step S3 is used to heat the structural adhesive sample, including:
[0027] Setting a temperature control program for the heating mechanism, wherein the temperature control program includes a second heating program and a second temperature rising program;
[0028] A temperature control program is set for the heating mechanism, wherein the temperature control program includes a second heating program and a second heating program; the second heating program controls the heating plate to be heated to 30°C-55°C; the second heating program controls the heating speed and duration of the heating plate to heat the heating plate to 55°C-110°C;
[0029] The pressing rate of the pressing mechanism is set to 0.3um / s-4.2um / s and the pressing time is set to 10min-60min;
[0030] The pressing mechanism drives the pressing plate and the second prefabricated plate to press down according to the set pressing rate and pressing time to squeeze the structural adhesive sample; wherein the pressing time set by the pressing mechanism is less than the heating time of the heating plate.
[0031] Optionally, the third prefabricated plate has a bearing surface and a baffle, the bearing surface is used to bear the structural adhesive sample, and the baffle is arranged on both sides of the third prefabricated plate and protrudes from the bearing surface;
[0032] When the pressing mechanism drives the pressing plate and the second prefabricated plate to press downward, the structural adhesive sample located on the bearing surface is squeezed out from both ends of the third prefabricated plate.
[0033] Optionally, placing the structural adhesive sample on the third prefabricated plate further comprises:
[0034] The structural adhesive sample is located between the second prefabricated board and the third prefabricated board, and a portion of the structural adhesive sample extruded from the end of the third prefabricated board is scraped off, so that the end surface of the structural adhesive sample is sloped.
[0035] Optionally, step S3 further includes:
[0036] A material plate having the same material, surface roughness and surface properties as those of a wind turbine blade is provided, and the material plate is cut into the second prefabricated plate and the third prefabricated plate.
[0037] The beneficial effects of the method for predicting the extrusion cracking behavior of the structural adhesive provided by the present invention are as follows:
[0038] 1. The present invention can accurately predict the extrusion cracking behavior of structural adhesives through simple rheological tests, and can quickly compare different structural adhesives to screen out the best formula of the structural adhesive.
[0039] 2. In order to avoid the influence of the structural adhesive samples on the prediction results due to the difference in sample quantity, the present invention firstly uses rheological testing to quickly screen out the structural adhesive samples that will not undergo extrusion cracking, and then uses a device that simulates the on-site bonding conditions of wind power structural adhesives to conduct extrusion experimental verification to improve the accuracy of the prediction.
[0040] 3. The prediction method provided by the present invention can collect the actual exothermic temperature of the structural adhesive sample, the pressure data of the structural adhesive sample when the relative position of the bonding surface changes, etc. during the test process, so as to have a deeper understanding of the mechanism of the occurrence of structural adhesive bonding defects.
[0041] 4. The prediction method provided by the present invention is helpful to determine the formula of structural adhesives and can guide the formula optimization of structural adhesives that experience extrusion cracking behavior.
[0042] 5. The prediction method provided by the present invention is less affected by human factors and has a high degree of parallelism. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A flow chart of a method for predicting extrusion cracking behavior of a structural adhesive according to an embodiment of the present invention;
[0044] Figure 2 A curve chart of first test data obtained by performing stress scanning on a structural adhesive sample according to an embodiment of the present invention;
[0045] Figure 3 A schematic diagram of the structure of a device for simulating on-site bonding of structural adhesives provided in an embodiment of the present invention;
[0046] Figure 4 A front view of the first test plate and the second test plate before the structural adhesive of the embodiment provided by the present invention is bonded;
[0047] Figure 5 This is a side view of the first test board and the second test board before the structural adhesive of the embodiment provided by the present invention is bonded.
[0048] Reference numerals:
[0049] 1. Pressing mechanism; 11. Pressing plate; 121. First supporting member; 122. Moving assembly; 1221. Moving member; 1222. Fixed member; 1223. Slide rail; 13. Power device; 131. Displacement electric cylinder; 132. Loading motor;
[0050] 14. Connecting piece; 2. Heating mechanism; 21. Heating plate; 22. Second supporting piece; 23. Support plate; 3. Second prefabricated board; 4. Third prefabricated board; 5. Structural adhesive sample; 51. Slope. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the usual meanings understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Unless otherwise specified, the "connection" described in this article can be a direct connection or an indirect connection, that is, connected through an intermediate.
[0052] In view of the problems existing in the prior art, an embodiment of the present invention provides a method for predicting the extrusion cracking behavior of a structural adhesive, referring to Figure 1 As shown, the prediction method includes:
[0053] S0: Preparation of structural adhesive samples.
[0054] In this step, the resin and the curing agent are uniformly mixed according to a certain mass ratio to prepare a structural adhesive sample.
[0055] It should be noted that each time before testing the structural adhesive sample, it is necessary to prepare the structural adhesive sample anew, because the prepared structural adhesive sample will undergo a curing reaction after a period of time, and it is impossible to predict after curing.
[0056] S1: performing a stress scanning test on the structural adhesive sample to obtain first test data.
[0057] The first test data includes a yield transformation curve and a yield stress value of the structural adhesive sample, and whether the structural adhesive sample is prone to cracking is determined based on the first test data.
[0058] In this step, a stress scanning test is performed on the structural adhesive sample using a stress scanning detector to obtain first test data including a yield transition curve and a yield stress value.
[0059] Specifically, when a rheometer is used to perform a stress scanning test on a structural adhesive sample, if the stress applied to the structural adhesive sample is greater than the yield stress value of the structural adhesive sample, and the yield transition curve of the structural adhesive sample does not undergo a significant mutation, then the structural adhesive sample is judged to be prone to cracking. If the stress applied to the structural adhesive sample is greater than the yield stress value of the structural adhesive sample, and the yield transition curve of the structural adhesive sample undergoes a significant mutation, then the structural adhesive sample is judged to be not prone to cracking.
[0060] S2: placing the structural adhesive sample on a rheometer test fixture; setting a temperature program and a pressing time and a pressing speed of the test fixture on the rheometer to perform an extrusion cracking test on the structural adhesive sample to obtain second test data.
[0061] In this step, the second test data includes whether the structural adhesive sample cracks during the extrusion process, the cracking time of the structural adhesive sample during the extrusion process, and the degree of cracking of the structural adhesive sample during the extrusion process. The extrusion cracking behavior of the structural adhesive sample is predicted based on the second test data.
[0062] Specifically, a material plate of the same material as that of the wind turbine blade is prepared in advance, and the surface roughness and surface properties of the material plate are the same as those of the wind turbine blade. The material plate is cut into a first disc-shaped prefabricated plate to simulate the actual bonding surface on the wind turbine blade, and then the two first prefabricated plates are fixed on the test fixture of the rheometer. Then, the structural adhesive sample is placed on the first prefabricated plate below, and then the temperature program of the rheometer and the pressing time and pressing speed of the test fixture are set. The rheometer will heat the structural adhesive sample according to the temperature program, and the test fixture will perform an extrusion cracking test on the structural adhesive sample according to the set pressing time and pressing speed, and record and observe the shape of the structural adhesive sample. When cracking occurs during the extrusion process of the structural adhesive sample, it is determined that the structural adhesive will crack.
[0063] It should be noted that the temperature program includes a first heating program and a first temperature rise program. The first heating program is used to control the heating of the rheometer so that the temperature of the structural adhesive sample reaches 30°C-55°C, and the first temperature rise program is used to control the heating of the rheometer so that the temperature of the structural adhesive sample rises to 55°C-110°C. In addition, the preheating time of the structural adhesive sample is set on the rheometer to 2min-30min. The pressing rate of the test fixture is 0.3um / s-4.2um / s, and the pressing time is 10min-60min.
[0064] S3: When the structural adhesive sample does not exhibit extrusion cracking behavior during the extrusion process, the structural adhesive sample is verified using a device that simulates on-site bonding of the structural adhesive to determine whether the predicted result is accurate.
[0065] It should be noted that the rheometer has a small test volume for structural adhesive samples, and the curing of wind power structural adhesive is a continuous heat release process. Under the same temperature program, the difference in the amount of structural adhesive samples will also affect the temperature of the actual structural adhesive samples. If only the rheometer is used to test the structural adhesive samples, when there is a large difference between the predicted amount of structural adhesive samples and the actual amount of structural adhesive samples during bonding, the predicted results will be inaccurate. Therefore, further verification of the structural adhesive samples is required.
[0066] Specifically, a device simulating on-site bonding of structural adhesive may be used to verify the structural adhesive sample to determine whether the predicted result is accurate.
[0067] Among them, the device for simulating on-site bonding of structural adhesive includes a pressing mechanism and a heating mechanism that are relatively arranged, the pressing mechanism has a pressing plate, and the heating mechanism has a heating disk. The second prefabricated board and the third prefabricated board are fixedly installed on the pressing plate and the heating disk respectively, and the sizes of the second prefabricated board and the third prefabricated board are larger than the size of the first prefabricated board. The structural adhesive sample is placed on the third prefabricated board on the heating disk, and the heating disk is used to heat the structural adhesive sample. Then the pressing mechanism drives the pressing plate and the second prefabricated board to press down, and the second prefabricated board on the pressing plate and the third prefabricated board on the heating disk squeeze the structural adhesive sample. The structural adhesive sample is verified by judging whether the structural adhesive sample after extrusion has cracking behavior.
[0068] It should be noted that the heating mechanism includes a temperature control system, and the temperature control program of the heating mechanism is set by the temperature control system. Among them, the temperature control program includes a second heating program and a second heating program. The second heating program controls the heating plate to heat to 30℃-55℃, and the second heating program controls the heating speed and duration of the heating plate to heat the heating plate to 55℃-110℃. In addition, the pressing rate of the pressing mechanism is set to 0.3um / s-4.2um / s, and the pressing time is 10min-60min. The pressing mechanism drives the pressing plate to press down according to the set pressing rate and pressing time to squeeze the structural adhesive sample. Among them, the pressing time set by the pressing mechanism is less than the heating time of the heating plate, which means that after the pressing plate is pressed down, the heating plate still heats the structural adhesive sample for a period of time.
[0069] In this embodiment, before each test, a structural adhesive sample to be predicted is first prepared, and then a stress scanning test is performed on the structural adhesive sample to obtain the first test data. The stability of the structural adhesive sample and whether it is prone to cracking are preliminarily judged based on the first test data. Subsequently, an extrusion cracking test is performed on the structural adhesive sample, and the extrusion cracking behavior of the structural adhesive sample is predicted based on the obtained second test data. It is possible to predict in advance whether the structural adhesive will crack, which is convenient for understanding the mechanism of structural adhesive defects, and the formula can be quickly optimized based on the mechanism of structural adhesive defects. In addition, different test methods are used to verify each other, which greatly improves the accuracy of the prediction.
[0070] In some specific embodiments, the method for predicting the extrusion cracking behavior of the structural adhesive provided by the present invention includes: selecting three resins with brand names TS380-R1, TS380-R2, and TS380-R3 from Daosheng Tianhe Materials Technology (Shanghai) Co., Ltd., and selecting three curing agents with brand names TS385-R1, TS385-R2, and TS385-R3 from Daosheng Tianhe Materials Technology (Shanghai) Co., Ltd.
[0071] Resin TS380-R1 and curing agent TS385-R1, resin TS380-R2 and curing agent TS385-R2, resin TS380-R3 and curing agent TS385-R3 were weighed at a mass ratio of 100:45 and placed in three 60 ml mixing cups respectively. Then the three mixing cups were placed in a mixer, and the mixer was mixed at 2000 rpm for 2 minutes to obtain the first structural adhesive sample (TS380-R1 / TS385-R1), the second structural adhesive sample (TS380-R2 / TS385-R2) and the third structural adhesive sample (TS380-R3 / TS385-R3).
[0072] refer to Figure 2 As shown, a rheometer is used to perform stress scanning tests on the first structural adhesive sample, the second structural adhesive sample, and the third structural adhesive sample to obtain yield transformation curves and yield stress values of the first structural adhesive sample, the second structural adhesive sample, and the third structural adhesive sample, respectively.
[0073] pass Figure 2 From the content, it can be seen that the yield transition curve of the first structural adhesive sample shows an obvious mutation after the applied stress value is higher than the yield stress value, and the viscosity value drops sharply, so it can be preliminarily judged that the first structural adhesive sample is prone to cracking under pressure. By observing the yield transition curve of the third structural adhesive sample, it can be seen that when the stress value is higher than the yield stress value, the viscosity value does not show an obvious mutation, and the entire yield transition process is relatively gentle. It can be preliminarily judged that the third structural adhesive sample is not prone to cracking. The yield transition process of the second structural adhesive sample is between the first structural adhesive sample and the second structural adhesive sample, and it can be judged that its cracking degree is also between the first structural adhesive sample and the second structural adhesive sample.
[0074] Furthermore, the rheometer includes a test fixture, and two disposable aluminum plates with a diameter of 40 mm are selected as the upper and lower clamps of the test fixture. Two first prefabricated plates with a diameter of 40 mm and a thickness of 2 mm are prepared using epoxy infusion resin composite materials, so that the first prefabricated plates are made of the same material as the wind turbine blade shell, and their manufacturing process and surface roughness are the same as the manufacturing process and surface roughness of the wind turbine blade shell. The two prepared first prefabricated plates are bonded to the two disposable aluminum plates on the test fixture. Then, the test fixture is used to perform rheological extrusion tests on the first structural adhesive sample, the second structural adhesive sample, and the third structural adhesive sample, respectively, and the entire pressing process is observed, and the experimental results are recorded one by one. Among them, the initial thickness of the first structural adhesive sample, the second structural adhesive sample, and the third structural adhesive sample can all be set to 5000um, the pressing rate of the test fixture is set to 2.78um / s, the pressing time is set to 15min, and the first heating temperature program set on the rheometer is constant temperature heating at 45°C for 35min, and the first temperature rise program is set to increase from 45°C to 85°C at a heating rate of 1°C / min.
[0075] It should be noted that the time for the test fixture to start running to extrude the first structural adhesive sample, the second structural adhesive sample, and the third structural adhesive sample is set at 15 minutes after the start of the first heating program, that is, when the temperature rises from 45°C to 60°C, the test fixture presses down at a moving speed of 2.78um / s and continues for 15 minutes.
[0076] According to the results of the extrusion test, it can be observed that the first structural adhesive sample has the most obvious cracking, with a large number of cracks and wide cracks. The second structural adhesive sample has obvious cracking behavior, but the degree of cracking is not as good as the first test sample, and the third structural adhesive sample did not crack after undergoing the rheological extrusion test. It can be seen that by using a rheometer to test the structural adhesive samples, the cracking behavior of each structural adhesive sample can be observed very intuitively, and it is consistent with the stress scanning test results, and the extrusion cracking behavior of each structural adhesive sample can be predicted very quickly.
[0077] On the other hand, an embodiment of the present invention provides a device for simulating on-site bonding of structural adhesives, referring to Figure 3 As shown, the device for simulating the on-site bonding of structural adhesive comprises a pressing mechanism 1 and a heating mechanism 2 which are arranged relatively to each other. The pressing mechanism 1 comprises a pressing plate 11 and a driving mechanism, the pressing plate 11 is connected to the driving mechanism, the driving mechanism is used to drive the pressing plate 11 to move, the pressing plate 11 is used to connect to the second prefabricated board 3, and the heating mechanism 2 comprises a heating disk 21, the heating disk 21 is arranged relatively to the pressing plate 11, the heating disk 21 is used to connect to the third prefabricated board 4, and can heat the third prefabricated board 4.
[0078] refer to Figures 3 to 5As shown, when the device is used to verify the structural adhesive sample 5, the structural adhesive sample 5 is placed on the third prefabricated board 4, the heating plate 21 heats the third prefabricated board 4 to transfer heat to the structural adhesive sample 5, and the driving mechanism drives the second prefabricated board 3 to move to extrude the structural adhesive sample 5, so as to achieve test verification of the structural adhesive sample 5.
[0079] Specifically, when the device is used to verify the structural adhesive sample 5, the heating mechanism 2 sets the temperature control program of the heating disk 21 through the control system, and the temperature control program specifically includes a second heating program and a second heating program. Among them, the second heating program is used to control the heating disk 21 to heat to 36°C-54°C, and the second heating program controls the heating speed and heating duration of the heating disk so that the heating disk is heated to 68°C-102°C, and then the heating disk 21 is heated according to the second heating program, and then the second prefabricated board 3 is fixed on the pressing plate 11, and the third prefabricated board 4 is fixed on the heating disk 21. When the temperature of the heating disk 21 reaches 36°C-54°C according to the second heating program, the structural adhesive sample 5 is placed on the third prefabricated board 4, and then the pressing plate 11 is loaded and pressed down, so that the second prefabricated board 3 and the third prefabricated board 4 cooperate to extrude the structural adhesive sample 5, and the heating disk 21 can be heated according to the second heating program so that the temperature of the heating disk 21 rises to 68°C-102°C until the test is completed.
[0080] The prediction results of the structural adhesive sample 5 are verified in advance by simulating the application scenario of the structural adhesive sample 5 in the laboratory through a device simulating on-site bonding of the structural adhesive, thereby ensuring the accuracy of the prediction method.
[0081] It should be noted that, since the structural adhesive sample 5 in this embodiment is applied to a wind turbine blade, the second prefabricated plate 3 and the third prefabricated plate 4 are prefabricated plates with the same material and thickness as the web of the wind turbine blade. The size of the second prefabricated plate 3 can be the same as the actual width of the web of the wind turbine blade, the size of the third prefabricated plate 4 can be larger than the size of the second prefabricated plate 3, and the third prefabricated plate 4 has a bearing surface for bearing the structural adhesive sample, and baffles can be provided on the left and right sides of the bearing surface to make the third prefabricated plate 4 present a "concave" shape. In this way, it can be ensured that when the second prefabricated plate 3 and the third prefabricated plate 4 press the structural adhesive sample 5, the excess structural adhesive squeezed out from the ends of the second prefabricated plate 3 and the third prefabricated plate 4 is scraped off, so that the end face of the structural adhesive sample 5 forms a slope 51, so as to truly simulate the on-site bonding of the structural adhesive, and it is also more conducive to observing whether the structural adhesive sample 5 cracks.
[0082] In some embodiments, reference Figure 3As shown, the driving mechanism includes a first support member 121 and a moving assembly 122. The pressing plate 11 is arranged at the bottom of the moving assembly 122. The moving assembly 122 is used to drive the pressing plate 11 to move horizontally. One end of the first support member 121 is connected to the top of the moving assembly 122, and the other end of the first support member 121 is used to connect to the telescopic end of the tensile machine. The tensile machine is used to provide power to drive the pressing plate 11 to telescopically move in the direction where the heating plate 21 is located.
[0083] In this embodiment, the driving mechanism realizes the up and down movement through an external tensile machine, thereby driving the second prefabricated plate 3 to extrude the structural adhesive sample 5. In some embodiments, the driving mechanism may include a tensile machine or a telescopic mechanism, which means that the device for simulating the on-site bonding of the structural adhesive sample 5 can realize the up and down movement of the pressing plate 11 without the help of an external power device.
[0084] Furthermore, the moving assembly 122 includes a moving member 1221, a fixed member 1222 and a slide rail 1223. The moving member 1221 is movably connected to the fixed member 1222 through the slide rail 1223, and the moving direction of the moving member 1221 is perpendicular to the direction of movement of the telescopic end, which means that the moving member 1221 can move horizontally. The pressing plate 11 is connected to the moving member 1221 through a plurality of connecting rods, and the first support member 121 is connected to the fixed member 1222. The fixed member 1222 is fixedly connected to one end of the connecting member 14, and the other end of the connecting member 14 is fixedly connected to the power device 13, and the power end of the power device 13 is connected to the moving member 1221.
[0085] In the present embodiment, the moving part 1221 and the fixed part 1222 are both square plate structures, and the power end of the power device 13 is connected to the moving part 1221 to drive the moving part 1221 to move horizontally, so that when the structural adhesive sample 5 is tested, a lateral pulling force can be applied to the structural adhesive sample 5, further simulating the scene of the structural adhesive sample 5 in actual use, so as to comprehensively test the structural adhesive sample 5. In addition, the power device 13 in the present embodiment includes a displacement electric cylinder 131 and a loading motor 132, the loading motor 132 is electrically connected to the displacement electric cylinder 131, and the loading motor 132 is used to control the moving speed of the displacement electric cylinder 131, and the power end of the displacement electric cylinder 131 is connected to the moving part 1221 to drive the moving part 1221 to move, so that the device can change the lateral moving speed of the moving part 1221 according to the test needs.
[0086] In some embodiments, the heating mechanism 2 further includes a second support member 22 and a support plate 23, the support plate 23 is connected to the heating disk 21, the support plate 23 is located at the bottom of the heating disk 21, and together with the heating disk 21, a cavity is formed, silicone oil is filled into the cavity, so that the upper surface of the silicone oil is in contact with the heating disk 21, and a temperature sensor is placed in a groove on the upper surface of the heating disk 21 to achieve temperature control of heating. When the silicone oil is insufficient, silicone oil is added to the cavity through a side pipeline. The top end of the second support member 22 is connected to the support plate 23, and the bottom end of the second support member 22 is used to connect to the base of the tensile machine.
[0087] In some embodiments, the device for simulating on-site bonding of structural adhesives also includes a temperature control box and a temperature sensor. The pressing mechanism 1 and the heating mechanism 2 are both arranged in the temperature control box. A temperature control unit is provided in the temperature control box. The temperature control unit is used to heat the temperature control box. The temperature sensor is used to detect the temperature inside the structural adhesive sample 5.
[0088] In this embodiment, the temperature control unit includes a heater and a cooler. The heater is used to heat the temperature control box to increase the temperature in the temperature control box, and the cooler is used to reduce the temperature in the temperature control box. By setting the pressing mechanism 1 and the heating mechanism 2 in the temperature control box, it is used to simulate the ambient temperature of the structural adhesive sample 5 during on-site bonding, so as to further increase the authenticity of the simulated environment. More importantly, when performing testing, a temperature sensor can be inserted into the structural adhesive sample 5 to detect the actual temperature in the structural adhesive sample 5, so as to more accurately understand the mechanism of the bonding defect behavior of the structural adhesive sample 5.
[0089] In some embodiments, the temperature of the test environment may be directly controlled by using a temperature control box of the tensile testing machine to simulate a real environment.
[0090] In order to facilitate the understanding of the device for simulating on-site bonding of the structural adhesive sample 5, the following will introduce a scenario of simulating on-site bonding of the structural adhesive sample by using a device for simulating on-site bonding of the structural adhesive sample.
[0091] refer to Figures 3 to 5As shown, in other embodiments, the heating mechanism 2 is provided with a second heating program and a second heating program. Among them, the second heating program is to control the heating plate 21 to heat to 45°C, and then maintain a constant temperature of 45°C for 35 minutes, and the second heating program is to control the heating plate 21 to heat from 45°C to 85°C at a heating rate of 1°C / min. Then, a plate with a size of 15cm×15cm is selected as the second prefabricated plate 3, and a plate with a size of 30cm×30cm is selected as the third prefabricated plate 4, and the left and right sides of the third prefabricated plate 4 are provided with 2cm×25cm baffles to make the third prefabricated plate 4 "concave". Then the second prefabricated plate 3 is fixed on the pressing plate 11, and the third prefabricated plate 4 is fixed on the heating plate 21. Then start the second heating program. When the temperature of the heating plate 21 reaches 45°C, debug the tensile machine. The tensile machine drives the second prefabricated board 3 down until it contacts the third prefabricated board 4. At this time, determine the zero position. Then the tensile machine drives the second prefabricated board 3 up. Then the structural adhesive sample 5 can be placed on the third prefabricated board 4. The thickness of the structural adhesive sample 5 is 20 mm. After preheating for 20 minutes, the tensile machine drives the second prefabricated board 3 to move to the -10 mm position and reset again. At this time, the second prefabricated board 3 and the third prefabricated board 4 squeeze the structural adhesive sample 5. Then, scrape off part of the structural adhesive sample 5 squeezed from both ends of the third prefabricated board 4, so that the structural adhesive sample 5 at both ends of the third prefabricated board 4 is presented in the form of a slope 51, and take a photo to save. Then cut out a 14 cm × 13 cm glass fiber cloth, evenly apply hand-paste resin on the glass fiber cloth, and cover the second prefabricated board 3, the slope 51 of the structural adhesive sample 5 and the third prefabricated board 4 with the glass fiber cloth coated with hand-paste resin. Set the tensile testing machine to start loading and pressing, the second pressing rate is 0.132mm / min, the loading and second pressing time lasts for 15 minutes and then stops, and continue heating until the verification test is completed.
[0092] Continue to refer Figures 3 to 5As shown, in some other embodiments, the heating mechanism 2 sets a second heating program and a second heating program through a control system. Among them, the second heating program is to control the heating plate 21 to heat to 45°C, and then maintain a constant temperature of 45°C for 35 minutes, and the second heating program is to control the heating plate 21 to rise from 45°C to 85°C at a heating rate of 1°C / min. Then, a plate with a size of 15cm×15cm is selected as the second prefabricated plate 3, and a plate with a size of 30cm×30cm is selected as the third prefabricated plate 4, and the left and right sides of the third prefabricated plate 4 are provided with 2cm×25cm baffles to make the third prefabricated plate 4 "concave". Then the second prefabricated plate 3 is fixed on the pressing plate 11, and the third prefabricated plate 4 is fixed on the heating plate 21. Then start the second heating program. When the temperature of the heating plate 21 reaches 45°C, debug the tensile machine. The tensile machine drives the second prefabricated board 3 down until it contacts the third prefabricated board 4. At this time, determine the zero position. Then the tensile machine drives the second prefabricated board 3 up. Then the structural adhesive sample 5 can be placed on the third prefabricated board 4. The thickness of the structural adhesive sample 5 is 20 mm. After preheating for 20 minutes, the tensile machine drives the second prefabricated board 3 to move to the -10 mm position and reset again. At this time, the second prefabricated board 3 and the third prefabricated board 4 squeeze the structural adhesive sample 5. Then, scrape off part of the structural adhesive sample 5 squeezed from both ends of the third prefabricated board 4, so that the structural adhesive sample 5 at both ends of the third prefabricated board 4 is presented in the form of a slope 51, and take a photo to save. Then cut out a 14 cm × 13 cm glass fiber cloth, evenly apply hand-paste resin on the glass fiber cloth, and cover the second prefabricated board 3, the slope 51 of the structural adhesive sample 5 and the third prefabricated board 4 with the glass fiber cloth coated with hand-paste resin. The tensile machine was set to start loading and pressing, with the second pressing rate being 0.132 mm / min. At the same time, the power device 13 drove the moving component 122 to move horizontally, with a horizontal movement rate of 0.0002 mm / s, and the whole process was recorded by video. The second pressing time was stopped after 15 minutes of loading, and heating was continued until the end of the test.
[0093] It should be noted that, during the above-mentioned test process, the tensile machine will record the positive pressure data of the structural adhesive sample 5 when the relative position of the bonding surface of the structural adhesive sample 5 changes. At the same time, the temperature sensor records the actual temperature of the structural adhesive sample 5 during the bonding test, which is convenient for understanding the cause of the bonding defects and serves as a guide for the subsequent optimization of the formula of the structural adhesive sample 5.
[0094] The above is only a specific implementation of the embodiment of the present application, but the protection scope of the embodiment of the present application is not limited thereto, and any changes or replacements within the technical scope disclosed in the embodiment of the present application should be included in the protection scope of the embodiment of the present application. Therefore, the protection scope of the embodiment of the present application should be based on the protection scope of the claims.
Claims
1. A method for predicting extrusion cracking behavior of a structural adhesive, characterized in that: The prediction method comprises: S0: Preparation of structural adhesive samples; S1: performing a stress scanning test on the structural adhesive sample to obtain first test data; The first test data includes a yield transition curve and a yield stress value of the structural adhesive sample, and whether the structural adhesive sample is prone to cracking is determined based on the first test data; S2: placing the structural adhesive sample on a rheometer test fixture; setting a temperature program and a pressing time and a pressing speed of the test fixture on the rheometer to perform an extrusion cracking test on the structural adhesive sample to obtain second test data; The second test data includes whether the structural adhesive sample cracks during the extrusion process, the cracking time of the structural adhesive sample during the extrusion process, and the cracking degree of the structural adhesive sample during the extrusion process. The extrusion cracking behavior of the structural adhesive sample is predicted based on the second test data.
2. The prediction method according to claim 1, characterized in that: The step S1 of determining whether the structural adhesive sample is prone to cracking according to the first test data includes: When the stress applied to the structural adhesive sample is greater than the yield stress value, and the yield transition curve does not undergo an obvious mutation, it is judged that the structural adhesive sample is not prone to cracking; When the stress applied to the structural adhesive sample is greater than the yield stress value and the yield transition curve undergoes an obvious mutation, it is determined that the structural adhesive sample is prone to cracking.
3. The prediction method according to claim 1, characterized in that: In the extrusion cracking test of step S2, a material plate having the same material as that of a wind turbine blade is provided, and the surface roughness and surface properties of the material plate are the same as those of the wind turbine blade; the material plate is cut into a first prefabricated plate, and the first prefabricated plate is fixed on a test fixture of the rheometer; The structural adhesive sample is placed on the first prefabricated board.
4. The prediction method according to claim 1, characterized in that: The step S2 further comprises: Setting a temperature program on the rheometer, wherein the temperature program includes a first heating program and a first temperature rising program; The first heating program is used to control the heating of the rheometer so that the temperature of the structural adhesive sample reaches 30°C-55°C, and the first heating program is used to control the heating of the rheometer so that the temperature of the structural adhesive sample rises to 55°C-110°C; Setting the preheating time of the structural adhesive sample on the rheometer to 2 min-30 min; The pressing rate of the test fixture on the rheometer is set to 0.3um / s-4.2um / s and the pressing time is set to 10min-60min. The test fixture performs an extrusion cracking test on the structural adhesive sample according to the set pressing rate and pressing time to obtain the second test data.
5. The prediction method according to claim 3, characterized in that: After predicting the extrusion cracking behavior of the structural adhesive sample according to the second test data, the method further includes step S3: When the structural adhesive sample does not exhibit extrusion cracking behavior during the extrusion process, the structural adhesive sample is verified using a device that simulates on-site bonding of the structural adhesive to determine whether the predicted result is accurate.
6. The prediction method according to claim 5, characterized in that: The device for simulating on-site bonding of structural adhesive comprises a pressing mechanism and a heating mechanism which are arranged opposite to each other, wherein the pressing mechanism has a pressing plate, and the heating mechanism has a heating disk; The step S3 comprises: fixing a second prefabricated plate on the pressing plate, fixing a third prefabricated plate on the heating plate, and the sizes of the second prefabricated plate and the third prefabricated plate are both larger than the size of the first prefabricated plate; The structural adhesive sample is placed on the third prefabricated plate, and the heating plate is used to heat the structural adhesive sample; the pressing mechanism drives the pressing plate and the second prefabricated plate to press down to squeeze the structural adhesive sample; The structural adhesive sample is verified by determining whether cracking occurs in the structural adhesive sample after extrusion.
7. The prediction method according to claim 6, characterized in that: The heating plate in step S3 is used to heat the structural adhesive sample, including: A temperature control program is set for the heating mechanism, wherein the temperature control program includes a second heating program and a second heating program; the second heating program controls the heating plate to be heated to 30°C-55°C; the second heating program controls the heating speed and duration of the heating plate to heat the heating plate to 55°C-110°C; The pressing rate of the pressing mechanism is set to 0.3um / s-4.2um / s and the pressing time is set to 10min-60min; The pressing mechanism drives the pressing plate and the second prefabricated plate to press down according to the set pressing rate and pressing time to squeeze the structural adhesive sample; wherein the pressing time set by the pressing mechanism is less than the heating time of the heating plate.
8. The prediction method according to claim 6, characterized in that: The third prefabricated plate has a bearing surface and a baffle, the bearing surface is used to bear the structural adhesive sample, and the baffle is arranged on both sides of the third prefabricated plate and protrudes from the bearing surface; When the pressing mechanism drives the pressing plate and the second prefabricated plate to press downward, the structural adhesive sample located on the bearing surface is squeezed out from both ends of the third prefabricated plate.
9. The prediction method according to claim 8, characterized in that: Placing the structural adhesive sample on the third prefabricated plate also includes: The structural adhesive sample is located between the second prefabricated board and the third prefabricated board, and a portion of the structural adhesive sample extruded from the end of the third prefabricated board is scraped off, so that the end surface of the structural adhesive sample is sloped.
10. The prediction method according to claim 6, characterized in that: The step S3 also includes: A material plate having the same material, surface roughness and surface properties as those of a wind turbine blade is provided, and the material plate is cut into the second prefabricated plate and the third prefabricated plate.
Citation Information
Patent Citations
Fatigue failure mode prediction method for composite material and metal rubber rivet mixed connection structure
CN116504334A
Risk assessment method for slip behavior after sizing of structural adhesive
CN116879110A